Following the Birth of a Nanoplasma Produced by an Ultrashort Hard-X-Ray Laser in Xenon Clusters - Yoshiaki Kumagai; Hironobu Fukuzawa; Koji Motomura; Denys Iablonskyi; Kiyonobu Nagaya; Shin-ichi Wada; Yuta Ito; Tsukasa Takanashi; Yuta Sakakibara; Daehyun You; Toshiyuki Nishiyama; Kazuki Asa; et al. (AMER PHYSICAL SOC, 2022)
X-ray free-electron lasers (XFELs) made available a new regime of x-ray intensities, revolutionizing the ultrafast structure determination and laying the foundations of the novel field of nonlinear x-ray optics. Although earlier studies revealed nanoplasma formation when an XFEL pulse interacts with any nanometer-scale matter, the formation process itself has never been decrypted and its timescale was unknown. Here we show that time-resolved ion yield measurements combined with a near-infrared laser probe reveal a surprisingly ultrafast population (similar to 12 fs), followed by a slower depopulation (similar to 250 fs) of highly excited states of atomic fragments generated in the process of XFEL-induced nanoplasma formation. Inelastic scattering of Auger electrons and interatomic Coulombic decay are suggested as the mechanisms populating and depopulating, respectively, these excited states. The observed response occurs within the typical x-ray pulse durations and affects x-ray scattering, thus providing key information on the foundations of x-ray imaging with XFELs.